Teaching through TikTok, YouTube, and Moodle: the instructional design and learner engagement of educational nano-videos - Saccucci, Franco; Saccucci, Brent (My University, 2026)
This study examined the use of educational nano-videos (short instructional video clips) ranging in length from 1 to 2½ minutes. Using a mixed-methods survey design in two rounds, data was collected from students across asynchronous and face-to-face delivery modes. The impetus for this study was influenced by cognitive load theory (Sweller et al., 1998), wherein our investigation assessed how minimalist instructional video design can enhance learner engagement by reducing extraneous information and enhancing content retention. Centred on the learner experience, students evaluated the videos and were asked about their preferred video platforms, ideal video length, and their perception of the effectiveness in reaching the learning outcomes. For preferred platforms, results showed a preference for YouTube in the face-to-face delivery section, while in the asynchronous classes, there was a preference for the video platform in the university’s learning management system (Moodle). Results also showed a preference for videos between 90 seconds and 4 minutes in length. The majority of respondents assessed the videos on a Likert scale from “not effective” to “very effective” in achieving learning outcomes. The qualitative feedback highlighted the importance of the video’s pace, clarity of fonts and colours, and limiting the video’s background music in video segments when dealing with complex material. The study’s findings highlighted the value of minimalist and clear nano-videos as a pedagogical tool necessary for today’s digitally engaged learner.
Keywords: nano-videos; cognitive load theory; ultra-short videos; nano-learning